Development of a novel method for 3D scientific datasets in ion dynamics - Mohamad Sharif, Johan; Abd. Latiff, Muhammad Shafie; Ngadi, Md. Asri (2006)
In physics, structure of glass and ion dynamics are ssentially based on statistical analysis of data acquired through experimental measurement and computer simulation [1, 2]. Invariably, the details of the structure-transport relationships in the data have been mistreated in favor of ensemble average [3, 4]. In this study, we demonstrate a visual approach of such relationship using surface-based visualisation schemes. In particular, we demonstrate a scientific datasets of simulated 3D time-varying model and examine the temporal correlation among ion dynamics. We propose a scheme that uses a three dimensional visual representation with colour scale for depicting the timeline events in ion dynamics and this scheme could be divided into two major part such as global and local time scale. With a collection of visual examples from this study, we demonstrate that this scheme may offer an effective tool for visually mining 3D timeline events of the ion dynamics. This work will potentially form a basis of a novel analysis tool for measuring the effectiveness of visual representation to assist physicist in identifying possible temporal association among complex and chaotic atom movements in ion dynamics.